Analyzing the Implementation of Local Wisdom-Based Learning in Early Childhood Education: The Case of Early Childhood Education - Efrida Ita; Melania Restintuta Ngonu (Journal of Nonformal Education, 2025)
Background - Early childhood education based on local wisdom is important to develop children’s potential holistically, nurture various aspects of their development, preserve cultural heritage, strengthen national identity, and at the same time make education more contextual and meaningful. Research Urgency - The urgency of this research lies in the need to preserve local wisdom in early childhood education amid the rapid influence of globalization. Current practices often emphasize academic achievement while neglecting cultural values and contextual learning. Without immediate efforts, there is a risk that younger generations will lose connection to their cultural identity. This study is therefore crucial to provide a holistic learning model that not only fosters children’s development but also strengthens cultural identity and ensures meaningful, context-based education. Research Objectives - This study aims to analyze the implementation of early childhood education based on local wisdom in PAUD Terpadu Citra Bakti and to formulate recommendations for a contextual and culturally responsive learning model that supports the holistic development of young children. Research Method - The research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving teachers, children, and parents. The data analysis technique used Miles and Huberman’s interactive model, which consists of data collection, data reduction, data display, and conclusion drawing. Research Findings - The findings reveal that the implementation of local wisdom-based learning has a positive impact on children. These positive impacts include introducing and familiarizing children with cultural values from an early age, enhancing active participation in learning activities, utilizing local culture as a contextual learning resource, and fostering the development of children’s abilities through various learning activities. Research Conclusion – The implementation of local wisdom-based learning in PAUD Terpadu Citra Bakti has proven to be an effective means of introducing, instilling, and preserving culture from an early age. Thus, local wisdom-based learning not only strengthens children’s cultural identity but also stimulates the development of cognitive, socio-emotional, language, and motor skills. Research Novelty/Contribution - The novelty of this research lies in its analysis of early childhood education practices that genuinely integrate local wisdom into the teaching and learning process. Rather than merely describing cultural values, this study examines how local wisdom is utilized as learning resources, teaching methods, and a means of fostering children’s holistic development. Thus, the research demonstrates that local wisdom can serve as a pedagogical approach that is relevant, contextual, and meaningful for early childhood education.